Institutional and Social Innovation for Sustainable Urban Development. - Mieg, Harald A. (Routledge studies in sustainable development., 2013)
Which new institutions do we need in order to trigger local- and global sustainable urban development? Are cities the right starting points for implementing sustainability policies? If so, what are the implications for city management? This book reflects the situation of cities in the context of global change and increasing demands for sustainable development. The book introduces core findings, new methods, and international experience related to sustainability innovations and the social transformation of cities, synthesizing insights from megacity research, sustainability science, an.